An open‐label study in healthy men to evaluate the risk of seminal fluid transmission of denosumab to pregnant partners. (5th December 2015) - Sohn, Winnie; Lee, Edward; Kankam, Martin K.; Egbuna, Ogo; Moffat, Graeme; Bussiere, Jeanine; Padhi, Desmond; Ng, Eric; Kumar, Sandeep; Slatter, J. Greg
Abstract : Aims: Denosumab is a fully human monoclonal immunoglobulin G2 antibody that inhibits bone resorption and increases bone mass and strength. The present clinical study assessed serum and seminal fluid pharmacokinetics following a single denosumab dose in healthy men, and evaluated whether denosumab in seminal fluid poses any risk to a fetus in the event of unprotected sexual intercourse with a pregnant partner. Methods: An open‐label, single‐dose study in 12 healthy men was conducted over a 106‐day period. Subjects received a single subcutaneous dose of 60‐mg denosumab on day 1. Serum and seminal fluid samples were collected at specified time points to assess denosumab pharmacokinetics. Adverse events were recorded. Results: Denosumab was measurable at low concentrations in seminal fluid (~2% of serum concentrations). The mean [standard deviation (SD)] maximum observed drug concentration (Cmax ) was 6170 (2070) ng ml –1 (serum) and 100 (81.9) ng ml –1 (seminal fluid). The median time to Cmax (tmax ) was 8 days (serum) and 21 days (seminal fluid). The mean (SD) area under the plasma concentration–time curve (AUC) from time zero to the time of the last quantifiable concentration (AUClast ) was 333 000 (122 000) dayng ml –1 (serum) and 5220 (4880) dayng ml –1 (seminal fluid). The mean (SD) Cmax and AUC ratios between seminal fluid and serum were 0.0217 (0.0154) and 0.0170 (0.0148), respectively. Using conservative assumptions for ejaculate volume (6 ml), vaginal absorption (100%) and placental transfer (100%), the measured mean denosumab seminal fluid Cmax would result in fetal exposure that was more than 110 times below the preclinically derived 'no effect level' for denosumab. Conclusions: These results indicate a negligible risk to a fetus exposed to denosumab via seminal fluid transfer to a pregnant partner.